Marine Microbial Communities of North and South Shelves of Iceland - Jégousse, Clara; Vannier, Pauline; Groben, René; Guðmundsson, Kristinn; Marteinsson, Viggó Thor (Frontiers in Marine Science, 2022)
The North Atlantic Ocean surrounds Iceland, influencing its climate and hosting a rich ecosystem that provides the Icelandic nation with economically valuable marine species. The basis of the Icelandic marine ecosystem consists of communities of diverse microorganisms including bacteria, archaea, and unicellular eukaryotes. While the primary production of Icelandic waters has been monitored since the 50s, there is limited knowledge of the taxonomic and metabolic diversity of the marine microorganisms in Icelandic waters based on molecular techniques. In this study, we conducted annual sampling at four hydrographic stations over several years to characterize marine microbial communities and their metabolic potential. Using 16S ribosomal RNA gene amplicon sequencing and metagenomics, we resolved the microbial community composition on the North and South Shelves of Iceland, analyzed its evolution from 2011 to 2018, identified frequently occurring taxa, and predicted their potential metabolism. The results showed correlations between the marine microbial community profiles and the water masses in spring, between the North and South Shelves of Iceland. The differences in marine microbial diversity appear to be linked to the average seawater temperature in the mixed surface layer at each sampling station which also constrains the relative abundance of photosynthetic microorganisms. This study set a baseline for the marine microbial diversity in Icelandic marine waters and identified three photosynthetic microorganisms – the cyanobacteria Synechococcus and two members of the Chlorophyta clade – as valuable indicator species for future monitoring, as well as for application in ecosystem modeling in context with research on climate change.